Call Boys: Drug Use and Sex Work Among Marginalized Young Men in a Philippine Port Community. (March 2018) - Lasco, Gideon
Marginalized young men are a familiar presence in the areas surrounding Philippine ports, selling food and refreshments to the thousands of passengers who come through daily. A closer look, however, reveals that they engage in many other activities as they participate in an informal economy where income opportunities skirt the boundaries between licit and illicit. One job many of them engage in is sex work: as "call boys, " they offer their sexual services to male clients. Many of them also use drugs, particularly shabu (methamphetamine). This article examines the relationship between sex work and drug use and situates it in the everyday lives of young men. The researcher conducted in-depth interviews and focus group discussions among 20 males aged 18–25 years old, and over a period of 12 months, "hung out" with them, observing their activities, and listening to their conversations. This ethnographic study, conducted 3 years before a violent "war on drugs" began to waged in the country, argues that the young men view drug use and sex work as pragmatic choices in their everyday economic lives. Drug use and sex work are also linked to their notions of masculinity and are fraught with risks and unintended consequences that they often overlook—even as they have their own notions of safety and risk. Understanding the intersections between sex work and drug use in relation to young people's "local moral worlds" and gender ideologies can help craft more effective drug policies in the Philippines.